Polypharmacy and oral health-related quality of life in older adults: a systematic review - Lelyana, Shelly; Agustina, Dewi; Hendrartini, Julita; Pramono, Dibyo (Universitas Padjadjaran, 2025)
Introduction:: Patient-centered care requires medical personnel to address not only physical illnesses but also the psychosocial well-being of patients. older adultsOlder adults often have medically complex conditions, including one or more chronic diseases, requiring the use of multiple medications (polypharmacy). Polypharmacy is a common problem among older adults, with a reported prevalence of 30% to 80%. Many prescribed medications can lead to xerostomia and hyposalivation, which negatively impact the quality of life , including Oral Health-Related Quality of Life (OHRQoL). This systematic review aims to determine the impact of polypharmacy on OHRQoL in older adults and explore strategies to optimize OHRQoL in this population. Method: The dataset of articles concerning polypharmacy and OHRQoL in older adults was compiled from Google Scholar, PubMed, Semantic, and OpenAlex. The search encompassed publication from 2019 to 2024. Five articles were selected for in-depth analyses, and variations in methodologies used by the researchers in these selected studies were identified and considered. Results: Patients with polypharmacy hyposalivation exhibited significantly higher scores of the Summated Xerostomia Inventory questionnaire (SXI-PL) (8.60 ± 2.56) and the Oral Health Impact Profile-14 (OHIP-14sp) (16.0 ± 15.8). A statistically significant association was found between hyposalivation and both SXI-PL and OHIP-14sp scores (p < 0.05). Elderly individuals on continuous medication demonstrated increased odds of self-reported xerostomia (OR: 2.3; 95% CI: 1.19-4.67; P = 0.009). Conclusion: This study demonstrates an association between polypharmacy and decreased oral health-related quality of life (OHRQoL) in older adults.